Posterior reversible encephalopathy syndrome. Case report and literature review - Dianarelys Villafuerte Delgado; Ernesto Pérez Martínez; Félix González Pérez (Revista Finlay)
Posterior reversible encephalopathy syndrome constitutes a transient clinical and radiological entity, with multiple risk factors in which endothelial injury and compromise in cerebral perfusion are the common characteristics. Brain magnetic resonance is the method of choice for diagnosis. This is the case of a 26-year-old woman with a personal history of apparent health, who after an eutocic delivery suffered hypovolemic shock, product of postpartum hemorrhage due to uterine atony resulting in subtotal obstetric hysterectomy, mechanical ventilation with triple vasoactive support; after a favorable progress, she began with severe headache and visual disorders, high blood pressure and presented two episodes of generalized tonic-clonic seizures. A skull/brain CT scan of was performed and brain magnetic resonance study was also requested. The case is presented because of the unusual nature of this type of entity in everyday medical practice.